ANALISIS PERBEDAAN RELEVANSI NILAI DAN ASIMETRI INFORMASI SEBELUM DAN SESUDAH KONVERGENSI IFRS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Esterlina, Cynthia; Lindrawati, Lindrawati (Widya Mandala Surabaya Catholic University, 2016)
IFRS is an international standard which has two main characteristics, namely fair value and principle based. The use of fair value resulted in financial report’s relevance, which resulting any differences in the value relevance of accounting information. In addi-tion, the characteristic of the principle-based IFRS requires more extensive disclosure to produce financial statements that are more faithful representation and it would also inflict a difference in information asymmetry. IFRS convergence in Indonesia has been initiated since January 1st, 2009 and was implemented on January 1st, 2012. Therefore, this study is aimed to analyze the difference between the value relevance and information asymmetry on the stage before and after the IFRS convergence. The re-sults showed that there is a difference in the value relevance of accounting information on the stage before and after the conver-gence of IFRS. In addition, there are differences in the asymmetry of information before and after the convergence of IFRS, there-fore the convergence of IFRS proved to enhance the value relevance of accounting information and decrease the asymmetry of information on manufacturing companies listed in Indonesian Stock Exchange so that the convergence of IFRS can improve the quality of financial statements because it helps the financial statements to be more relevance and faithful representation.